Potential of Micro Hydro for Electricity Supply in Remote Areas of Singajaya, South Garut - Rohmat, Dede; Setiawan, Iwan; Suhendro, Suhendro; Kamila, Raksa Salat; Slamet, Edwin (Universitas Lampung, 2024)
The issue of electricity demand in remote areas is the focus of this research. One proposed alternative solution is to provide electricity by harnessing natural potential, such as using hydropower through micro hydro systems. This study aims to (1) analyze the electricity supply in Singajaya District, Garut Regency, (2) assess the conditions of remote areas based on the non-electrification ratio of villages, (3) evaluate the potential of Micro Hydro Power Plants (MHPP), and (4) analyze the distribution of this potential in the region. Singajaya District has a high non-electrification ratio, particularly in villages such as Sukamulya, Pancasura, and Sukawangi. The use of renewable energy through MHPP is seen as a solution to enhance electricity availability in these remote areas. This research employs a spatial approach based on Geographic Information Systems (GIS) to map potential sites for MHPP development, along with field data including rainfall, water discharge, and topography. The findings of the study indicate that (1) the electricity supply in Singajaya District is still limited, especially in remote areas that only receive 450 W, while in central areas of the district, capacity can exceed 450 W; (2) the conditions in remote areas of Singajaya District are characterized by high non-electrification ratios, with Sukamulya at 34.32%, Pancasura at 32.23%, and Sukawangi at 31.28%, making these three villages priorities for intervention; (3) six key locations were identified with significant capacity for electricity development, with a total potential generation of 170.18 kW; and (4) the distribution of MHPP potential, characterized by high water discharge and suitable elevation for water flow, could address electricity access for 19.22% of households that currently lack electricity. Keywords: Electricity Supply; Mircro Hydro; Remote Area; Renewable Energy Potential